2015
DOI: 10.1371/journal.pone.0132420
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic Profiling of Cardiac Hypertrophy and Fatty Heart Induced by Long-Term High-Energy Diet in Bama Miniature Pigs

Abstract: A long-term high-energy diet affects human health and leads to obesity and metabolic syndrome in addition to cardiac steatosis and hypertrophy. Ectopic fat accumulation in the heart has been demonstrated to be a risk factor for heart disorders, but the molecular mechanism of heart disease remains largely unknown. Bama miniature pigs were fed a high-fat, high-sucrose diet (HFHSD) for 23 months. These pigs developed symptoms of metabolic syndrome and showed cardiac steatosis and hypertrophy with a greatly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
19
0
2
Order By: Relevance
“…Xia et al fed a HFHSD to Bama minipigs to induce obesity [36]. They found that these obese pigs developed the metabolic syndrome, and showed cardiac steatosis and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al fed a HFHSD to Bama minipigs to induce obesity [36]. They found that these obese pigs developed the metabolic syndrome, and showed cardiac steatosis and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Early activation of STAT3 is evident in the heart in response to β-adrenergic receptor agonist treatment and cardiac specific STAT3 deletion led to increased cardiac hypertrophy, necrosis, and apoptosis after chronic β-adrenergic stimulation [13]. Obesity also has effects on cardiac STAT3 expression, in that cardiac STAT3 expression was differentially regulated in Bama miniature pigs fed a long-term high-energy diet compared to controls [14]. The suppressor of the cytokine signaling family (SOCS3) acts as a negative regulator of STAT3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…4C. The kidneys and hearts of the 320 animals in the Tg HFHS group also weighed significantly more (p<0.01) than those of the 321 animals in the other groups, similar to findings reported in previous research using a miniature 322 pig model of early-stage diabetes Xia et al 2015). Table 1.…”
supporting
confidence: 86%